Corpos (in)capazes: análise de conteúdo das regulamentações da política de inclusão da pessoa com deficiência no Brasil (2015-2021) - Reis, Daniela Ferreira dos (2022)
With the Brazilian Law of Inclusion we see in Brazil a policy based on the recognition of Disability and state intervention to reduce the social barriers that prevent independence. At the same time, economic, social, and political crises occur in the country that lead to the expansion of the neoliberal discourse of cutting spending on social policies. We question how neoliberalism fosters the regulatory structures of this inclusion policy created from the aforementioned law. As a general objective, we analyze the materialization of the neoliberal discourse in the content of the regulations by the national Executive Branch of the inclusion policy of the person with disabilities in Brazil in the period from 2015 to 2021. In the first chapter, we describe the methodology of thematic content analysis used in the final section. To this end, in the second and third chapters we outline the context of public policies for people with disabilities in Brazil and the construction of the category disability in the social-historical process with emphasis on the forms of representation, guardianship, definition (medical and social) and feminist studies. Through the theoretical assumptions of Marx's class struggle, Foucault’s biopolitics and Clara Valverde's "Radical Empathy", in the proposed documentary analysis, we came to the conclusion that, despite the principles of the Inclusion paradigm indicating towards the enlargement of the number of subjects and distinct body realities understood as people with disabilities, the neoliberal dictum of reducing the contingent of beneficiaries to reduce public spending prevails. Based on independence, the regulation and implementation of the policy ends up consenting to the situation of vulnerability, poverty, indigence and labor precarization to which people with disabilities who are dependents are subjected, who remain without access to a broad assistance policy based on care.